TINJAUAN LITERATUR TENTANG KEPUASAN KERJA, KETERIKATAN KERJA DAN KINERJA PENDIDIK - Muhammad Bagus Firmansyah; Dewi Retno Suminar; Nur Ainy Fardana (Khazanah Pendidikan, 2021)
This study examines teacher performance by looking at two factors, namely job satisfaction and job engagement. This exploratory qualitative study uses a literature review perspective with various sources taken from journals, online information, books to the previous research findings. This subject search only focused on the words job satisfaction, job engagement, and job performance as the search keywords. This study found that teachers can produce good learning because of the satisfaction of the results of the process that has been carried out. The satisfaction obtained also cannot be separated from a solid inner bond to the organization. So that the relationship between the three is very close in producing good quality education